Prevalence and Risk Factors of New-Onset Atrial Fibrillation and Its Role in the Prognosis of Critically Ill Patients: New-Onset Atrial Fibrillation in Critically Ill Patients - Saeed Golami Garab; Mohammad Javad Abdolhay; Alireza Gandomi-Mohammadabadi; Javad Balasi; Mohammad Amin Abbasi (Publisher: Shahid Beheshti University of Medical Sciences)
Introduction: Atrial fibrillation (AF) is the most prevalent dysrhythmia in the intensive care unit (ICU). This study aimed to assess the prevalence, clinical outcomes, and risk factors of new-onset AF in patients admitted to ICU, concerning mortality and length of stay.Methods: This cohort study consisted of patients above 18 years old admitted to the ICU of Firoozabadi hospital in 2019_2020. New-onset AF diagnosis was confirmed by ECG electrographic changes watched by cardiologists in 24 hours for each patient. Patients were divided into two groups: without new-onset AF [171 patients, 54.4% men, age: 65.09 (18–97) years] and with new-onset AF [23 patients, 52.2% men, age: 79 (55–95) years]. Clinical and laboratory features, including neutrophil-to-lymphocyte ratio (NLR) and platelet-to- lymphocyte ratio (PLR), were compared between the groups.Results: Among 194 patients, 118 (61%) were survivors, and 76 (39%) were non-survivors. Twenty-three patients (11.9%) developed new-onset AF. The AF group was significantly older than those in the no AF group (AF vs. no AF: 79 ± 11.5 years vs. 65 ± 20 years, P = 0.02). ICU survivors had a significantly shorter ICU stay than non-survivors (6 ± 0.5 days versus 13.6 ± 1.9 days, P < 0.001). Also, patients with new-onset AF had longer ICU stay (AF vs. no AF: 15.5 ± 10.9 days vs. 7.8 ± 10.6 days, P = 0.02). Patients who developed new-onset AF in the ICU had not greater in-hospital mortality (AF vs. no AF: 16.4% vs. 9.6%, P > 0.05). The NLR of AF and no AF subjects were 16.7 ± 12.6 and 11.6. ± 14.9, respectively (P = 0.008). There was no significant difference between the PLR of the AF group (284.6 ± 211.8) and no AF group (264.8 ± 204.8) (P = 0.7).Conclusions: Atrial fibrillation may not be independently associated with hospital mortality. NLR is a predictor of new-onset AF in critically ill patients.